Utility of β-diketones in heterocyclic synthesis: Synthesis of new tetrahydro-pyrimidinethione, pyrazole, thiophene, dihydropyridine, dihydropyrane, pyridazine derivatives and investigation of their antimicrobial activity - Reheim, Mohamed Ahmed Mahmoud Abdel; Hafiz, Ibrahim Saad Abdel; Mohamed, Safaa (European Journal of Chemistry, 2016)
A series of many important diverse number of fused heterocyclic systems were prepared from the reaction of 1-(2-hydroxynaphthalen-1-yl)-3-phenylpropane-1,3-dione with some bifunctional nucleophiles, these reactions mainly proceed via condensation of 1-(2-hydroxynaphthalen-1-yl)-3-phenylpropane-1,3-dione with the aldehydic function followed by nucleophilic attack. Structures of the new compounds were established by elemental analyses and spectral data. Some of the products were also screened in vitro for their antimicrobial activity.